Effets antimicrobiens de l'extraits aqueux de Thymus vulgaris(Thym) récolté dans la région de SETIF sur la qualité et la stabilité d'un lait alicament fermenté type yaourt ferme - ZAHAF, Leila; MEFTAH, Hafeda (My University, 2017)
Our experimental study is based on the effect of variation of the incorporation rates of water extract of Thymus vulgaris on the evolution of the microbiological and organoleptic physico-chemical parameters of firm fermented milks during the fermentation period and of post-acidification. The pH and acidity of the fermented milks are not affected by the addition of thyme extract. Fermented milks with and without thyme extracts maintained a normal acidity of less than 150 ° D until the end of the post-acidification period on the 21st day. The viscosity of the fermented milks at 2 and 4% of aqueous extract of thyme remains comparable to the control, the addition of thymus extract seems to reduce the number of Strepococus thermophlis and Lactobacillus bulgaricus in the fermented milks as compared to the control. However, the number of these specific yoghurt germs remains close to the normal of 106 live organisms / ml in the experimental tests. At the end, the best results of taste, cohesiveness and adhesiveness are detected at the level of the sample prepared at a rate of 2% aqueous extract of Thymus vulgaris.
Keywords: Laits fermenté; thym; yaourt; qualité; extrait; Fermented milk; thyme; yogurt; quality; extract